Current status and breakthroughs in treating advanced non-small cell lung cancer with EGFR exon 20 insertion mutations - Hu, Meng; Zhong, Congying; Wang, Jiabing; Chen, JinQin; Zhou, Tao (Frontiers in Immunology, 2024)
Recently, targeted therapy and immunotherapy have emerged as effective treatment options for non-small cell lung cancer (NSCLC). This progress has been facilitated by the rapid development of diagnostic and therapeutic technologies and the continuous research and development of new drugs, leading to a new era in precision medicine for NSCLC. This is a breakthrough for patients with common mutations in the human epidermal growth factor receptor (EGFR) gene in NSCLC. Consequently, the use of targeted drugs has significantly improved survival. Nevertheless, certain rare genetic mutations are referred to as EGFR exon 20 insertion (ex20ins) mutations, which differ in structure from conventional EGFR gene mutations, namely, exon 19 deletion mutations (19-Del) and exon 21 point mutations. Owing to their distinct structural characteristics, patients harboring these EGFR ex20ins mutations are unresponsive to traditional tyrosine kinase inhibitor (TKI) therapy. This particular group of patients did not fall within the scope of their applicability. However, the activating A763_Y764insFQEA mutation elicits a more pronounced response than mutations in the near and far regions of the C-helix immediately following it and should, therefore, be treated differently. Currently, there is a lack of effective treatments for EGFR ex20ins mutations NSCLC. The efficacy of chemotherapy has been relatively favorable, whereas the effectiveness of immunotherapy remains ambiguous owing to inadequate clinical data. In addition, the efficacy of the first- and second-generation targeted drugs remains limited. However, third-generation and novel targeted drugs have proven to be effective. Although novel EGFR-TKIs are expected to treat EGFR ex20ins mutations in patients with NSCLC, they face many challenges. The main focus of this review is on emerging therapies that target NSCLC with EGFR ex20ins and highlight major ongoing clinical trials while also providing an overview of the associated challenges and research advancements in this area.